Active and total rosette forming t-lymphocytes in lepromatous and tuberculoid leprosy. - Tolentino, Lolita E. (1983)
T cell isolation and enumeration by the E-rosette Test was done on 10 Lepromatous Leprosy (LL) and 8 tuberculoid leprosy (TT) patients. The test was used to assess Cell Mediated Immunity (CMI) among the leprosy patients. The defect in CMI of LL patients was shown by 2 criteria: 1) the failure of patients to elicit a delayed type hypersensitivity reaction to lepromin. TT patients gave positive reactions. 2) Histopathological examination of skin biopsies of the confirmed LL patients showed that they had poor lymphocytic responses. TT patients had good lymphocytic responses shown by the presence of lymphocytic granuloma in their skin lesions. Results of E-rosette test showed that the Active Rosette Forming Cell (A-RFC) subpopulation of LL patients (24.43 + 3.32) was comparable with normal individuals (23.69 + 5.62). On the other hand, the A-RFC subpopulation of TT patients (29.16 + 2.02) was higher than both LL patients and normal individuals. The Total Rosette Forming Cells (T-RFC) of LL patients (50.23 + 2.20) was significantly lower compared to that of TT patients (58.64 + 4.06) and normal individuals (60.02 + 3.33). The T-RFC of TT patients and normal individuals were comparable. These data show that the CMI of the LL patients was defective while that of the TT patients was functional. The defect in CMI of LL patients was due to a significant reduction in T-RFC. A probable functional defect of the A-RFC subpopulation of LL patients was also indicated.
Thesis (MS Public Health, Medical Microbiology)--University of the Philippines Manila.
Keywords: Leprosy; T cells; Cellular immunity